Endoscopy-Intravascular Treatment Combination for Duodenal Ulcer Hemorrhages Caused by Small Hepatic Pseudoaneurysms: A Case Report - Xiao P; Guo M; Zhu L (Dove Medical Press, 2024)
Peiguang Xiao,1 Maodong Guo,1 Lujian Zhu2 1Department of Gastroenterology, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, People's Republic of China; 2Department of Infectious Diseases, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, People's Republic of ChinaCorrespondence: Lujian Zhu, Department of Infectious Diseases, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, People's Republic of China, Email zhulj_brave@163.comAim: Significant gastrointestinal hemorrhages, resulting from long-term compression of the duodenum by a hepatic pseudoaneurysm (HAPA), is an extremely rare condition. In fact, when the pseudoaneurysm is small in diameter, diagnosis can be particularly challenging. Timely and effective diagnosis and treatment is therefore of great significance, and in this case, endoscopy, combined with intravascular therapy, can provide an effective approach, especially since it removes the need for surgery while yielding favorable outcomes.Case Summary: A 75-year-old old man presented to the hospital's emergency department with hematemesis and black stool. Despite conservative treatments such as "acid suppression, fluid resupply, hemostasis and blood transfusion", no significant improvement was noted. Emergency gastroscopy subsequently revealed an ulcer in the duodenal bulb (Figure 1), with an exposed thrombotic head and active bleeding on the surface. In addition, abdominal computed tomography (Figure 2) showed no obvious HAPA manifestations. After unsuccessful endoscopic hemostasis, angiography was performed (Figure 3) and a pseudotumor-like dilatation measuring 5.56 mm in diameter was found at the distal end of the proximal branch vessel of the common hepatic artery. Following spring coil embolization (Figure 4), the patient's condition improved and he was discharged from the hospital, with a follow-up after six months showing no signs of recurrence or complications.Conclusion: Duodenal ulcer hemorrhages due to small hepatic pseudoaneurysms are very rare, with endoscopic intervention being effective for such cases.Keywords: hepatic artery pseudoaneurysm, endovascular treatment, gastroscopy, duodenal ulcer, bleeding, case report